Springer Handbook of Electronic and Photonic Materials - Kasap, Safa; Capper, Peter (Springer International Publishing : Imprint: Springer, 2017)
The second, updated edition of this essential reference book provides a wealth of detail on a wide range of electronic and photonic materials, starting from fundamentals and building up to advanced topics and applications. Its extensive coverage, with clear illustrations and applications, carefully selected chapter sequencing and logical flow, makes it very different from other electronic materials handbooks. It has been written by professionals in the field and instructors who teach the subject at a university or in corporate laboratories. The Springer Handbook of Electronic and Photonic Materials, second edition, includes practical applications used as examples, details of experimental techniques, useful tables that summarize equations, and, most importantly, properties of various materials, as well as an extensive glossary. Along with significant updates to the content and the references, the second edition includes a number of new chapters such as those covering novel materials and selected applications. This handbook is a valuable resource for graduate students, researchers and practicing professionals working in the area of electronic, optoelectronic and photonic materials.
Keywords: Materials science.; Solid state physics.; Spectroscopy.; Microscopy.; Electronics.; Microelectronics.; Optical materials.; Electronic materials.; Materials -- Surfaces.; Thin films.; elektronické knihy; electronic books